Genetic Polymorphisms at TNF-Alpha Receptors Associated some Autoimmune Diseases and Response of Anti-TNF Biologics: Review - Alhilali, Dhulfiqar; Mohammed , Samer (Iraqi Journal of Pharmaceutical Sciences, 2024)
Some genetic factors are not only involved in some autoimmune diseases but also interfere with their treatment, Such as Crohn’s disease (CD), Rheumatoid Arthritis (RA), ankylosing spondylitis (AS), and psoriasis (PS). Tumor Necrosis Factor (TNF) is a most important pro-inflammatory cytokine, which has been recognized as a main factor that participates in the pathogenesis and development of autoimmune disorders. Therefore, TNF could be a prospective target for treating these disorders, and many anti-TNF were developed to treat these disorders. Although the high efficacy of many anti-TNF biologic medications, the Patients’ clinical responses to the autoimmune treatment showed significant heterogeneity. Two types of TNF receptor (TNFR); 1 and 2, it classified into two superfamilies; TNF-superfamily of ligands (TNFSF) (19 ligands) and TNF receptor superfamily (TNFRSF) (29 receptors). This review aims to provide an overview of the impact of genetic polymorphism on TNF alpha receptors on the response to anti-TNF biologics. Several single nucleotide polymorphisms (SNPs) recorded in the TNFRs gene on various immune system cells may affect the lower corresponding TNFRs gene expression. The present review summarized the studies that highlighted the role of heterogeneity in varying the response of patients. Many researchers indicated SNPs’ effect on the response of autoimmune patients to treatment with anti-TNF biologic medications, while other studies did not find a correlation. In conclusion, TNF is involved in several diseases such as CD, RA, AS, and PS; there was a link between TNFRs polymorphism and non-responsiveness to anti-TNF-α medications.